2016
DOI: 10.1007/s10483-016-2100-9
|View full text |Cite
|
Sign up to set email alerts
|

Analytical solution approach for nonlinear buckling and postbuckling analysis of cylindrical nanoshells based on surface elasticity theory

Abstract: The size-dependent nonlinear buckling and postbuckling characteristics of circular cylindrical nanoshells subjected to the axial compressive load are investigated with an analytical approach. The surface energy effects are taken into account according to the surface elasticity theory of Gurtin and Murdoch. The developed geometrically nonlinear shell model is based on the classical Donnell shell theory and the von Kármán's hypothesis. With the numerical results, the effect of the surface stress on the nonlinear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The accepted higher order theories employed to analyze the size scaling in microstructures are mainly micropolar theory [106], surface elastic theory [107], couple stress theory [108], strain gradient theory [109], nonlocal theory [110] and hybrid model like nonlocal strain gradient theory [111].…”
Section: Introductionmentioning
confidence: 99%
“…The accepted higher order theories employed to analyze the size scaling in microstructures are mainly micropolar theory [106], surface elastic theory [107], couple stress theory [108], strain gradient theory [109], nonlocal theory [110] and hybrid model like nonlocal strain gradient theory [111].…”
Section: Introductionmentioning
confidence: 99%
“…Singh and Yadava [23] investigated the influence of geometric nonlinear high-order terms caused by neutral axis shift on microcantilever response, and revealed that the influence of higher order deformation terms on the system response should be considered in the case of relative large deformation. Based on the classical Donnell's shell theory and von Karman's hypothesis, Ansari et al [24] discussed the surface stress effect on the static nonlinear buckling and postbuckling behaviors of nanoshells, and illustrated the influence of the surface residual tension and radius-to-thickness ratio. Zhang et al [17] thoroughly compared the differences of static deflection predicted by three different equivalent surface stress models.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, researchers have recently begun to use continuum theories which take the effect of material length scale (MLS) parameter into consideration. Those theories include non-local elasticity theory [1][2][3][4][5][6][7][8], couple stress theory [9][10][11][12][13][14][15][16][17][18], strain gradient theory [19][20][21][22], and surface stress theory [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%